Not wholly free : the concept of manumission and the status of manumitted slaves in the ancient Greek world - Zelnick-Abramovitz, Rachel. (Mnemosyne, Supplements, 2005)
Not Wholly Free is a comprehensive study of manumission in the Greek world, based on a thorough appraisal of the extant evidence and on a careful examination of manumission terminology. R. Zelnick-Abramovitz investigates the phenomenon of manumission in all its aspects and features, by analyzing modes of manumission, its terminology, the group composition of manumittors and freed slaves, motivation, procedures and conditions of manumission, legal actions and laws concerning manumitted slaves, and the latter's legal status and position in society. A very important work for all those interested in social history of ancient Greece , slavery, and manumission, as well as ancient historians and classical philologists.